Pengembangan Media Pembelajaran Komik Adat Ngayikka Berbasis Model Project Based Learning (PjBL) Dan Profil Kemampuan Menulis Teks Narasi - Desva Karina Karina; Abdul Muktadir; Gumono Gumono (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2026)
This research was motivated by the low narrative writing skills of elementary school students, particularly in developing ideas, organizing story structures coherently, and using appropriate language features. This condition is caused by learning activities that are still dominated by conventional methods and the limited use of engaging and contextual learning media. Students need visual and interactive learning media, while teachers require instructional media that support active learning and integrate local wisdom values. Therefore, this study aimed to develop comic-based learning media integrating the local wisdom of Adat Ngayikkah using the Project Based Learning (PjBL) model in teaching narrative writing to fourth-grade students. This study employed a development research method with a combination of quantitative and qualitative approaches. The research subjects consisted of 17 fourth-grade students at MI Al-Ikhlas Tanjung Sakti. The research instruments included expert validation sheets, teacher and student response questionnaires, and narrative writing skill tests. The results showed that students’ initial narrative writing ability was still low, with a mastery percentage of 23.5% (4 students achieved mastery). After the implementation of the Adat Ngayikkah comicbased learning media using the Project Based Learning model, the mastery percentage increased to 52.9% (9 students achieved mastery). Student responses to the comic media were categorized as very good with a percentage of 100%, and teacher responses indicated positive perceptions of the media use. Expert validation results showed that the comic media had a very high level of validity, with a material validity coefficient of 1.00, language validity of 0.89, and graphic validity of 0.89. Therefore, the Adat Ngayikkah comic-based learning media using the Project Based Learning model is feasible to be used as an alternative learning medium in Indonesian language instruction to improve elementary school students’ narrative writing skills.